(untitled) (Journal of Education and Development, 2023)
Participatory Action Research (PAR) is a research approach that utilizes collaborative relationships between researcher and stakeholders in order to solve a problem and generate knowledge (Coghlan & Brannick, 2010). Within the engineering space, PAR is beginning to gain steam and approval as a valid approach to research. More specifically, PAR is an ideal approach to understanding the experiences of marginalized populations. It can be argued that PAR methods and more feminist approaches are necessary within an engineering context, if we hope to make progress in regard to equity and inclusion in the engineering field. This paper provides an overview of PAR, while also discussing the need for positionality and reflection embedded in the research process. Each of the authors share a narrative reflection on their experiences within the PAR space and the challenges that accompany the action implementation phase of PAR. Additionally, example action items from a recent study are shared to provide context to the feasibility of PAR action. The goal of this paper is to raise awareness around PAR as a preferred approach when working with marginalized populations and the necessary resources researchers need to execute action items.